Effects of Giving Asam Gelugur Leaf Meal in Non-Conventional Rations on Carcass Percentage and Carcass Composition of Male and Female Ducks in Grower Phase - Dewi Wahyuni; Burhanudin Malik; Elis Dihansih (Universitas Djuanda, 2021)
Ducks are still less liked by consumers because the quality of production is still low compared to broilers. To improve this quality, additional feed can be in the form of herbs which are thought to have content for this. Asam gelugur leaves contain hydroxycitric acid and active substances that act as antioxidants. So that it is expected to improve the quality of the carcass. The purpose of this study was to examine the effect of giving asam gelugur leaf meal on the percentage and composition of male and female ducks in the grower phase. The study was conducted for 2 months in the Poultry Farm of Faculty of Agriculture, Djuanda University. The 40 grower ducks consist of male and female. Fourty male and female grower ducks were allocated into a 2 x 4 completely randomized factorial design. Factor A consisted of sexes (male and female) and factor B consisted of levels of asam gelugur leaf meal inclusion in rations (0, 2, 4, and 6%). five replicates were used for each treatment. The variables observed were slaughter weight, carcass weight, carcass percentage, commercial cut percentage of carcass and duck carcass composition. The results showed that there was no interaction and there was no significant difference (P> 0.05) from giving asam gelugur leaf meal to carcass percentage, carcass commercial cut percentage and duck carcass composition. The conclusion of this study is that giving asam gelugur leaf meal to males and females can maintain the quality of the carcass and the composition of the local duck carcass.